ORGANIZATION OF ISLAMIC COOPERATION RESPONSES ON THE ISRAEL AGGRESION AND THE UNITED STATES EMBASSY RELOCATION TO JERUSALEM - Afifah Ayumia; Putri Andini; Raden Muhamad Mahardika (Faculty of Law Universitas Lampung, 2022)
The aggression carried out by Israel against the Palestinian people and the declaration of Jerusalem as the capital of Israel with the relocation of the US Embassy received the attention of the OIC. As an organization committed to protecting Muslims' human rights, the OIC has the responsibility to take care of the human rights violations that occurred in Palestine. The objectives of this paper are to find out the OIC's role in maintaining Muslim peace in the world, how the OIC's response to Israeli aggression against the Palestinian people, and the relocation of the US Embassy to Jerusalem. The research method used in writing this journal is normative legal research, with historical approach to find out the beginning of the conflict between Palestine and Israel and an analytical approach to finding out the efforts made by the OIC for Israel's aggression against the Palestinian people and the United States Embassy relocation to Jerusalem under the provisions of international law.